Effectiveness of Passing Technique Skills Through Exercise Methods for SSB Imam Bonjol Padang U 13 Athletes - Rahmalia, Apriyanti; Arvandi, Yulio; Mardius, Ali; Faridatul‘Ala; Ningrum, Desy Tya Maya (Universitas PGRI Palembang, 2024)
Problems: The problem in this research is that the passing skills of the Imam Bonjol U-13 Football School athletes are still low. Purpose: The aim of this research is to determine the effectiveness of passing technique skill through exercise methods for SSB Imam Bonjol U 13 athletes. Methods: The type of research is quasi experiment. Results: The results of this research are: 1) There is significant effectiveness of passing technique training through a series of training approaches for Imam Bonjol U-13 Football School athletes (tcount = 2.02 > ttable 1.76). Conclusion: Based on the research results, a series of training approach can improve passing technique skills according to the U-13 age classification, so further research needs to be carried out to examine at a higher age. To add other factors that can influence the results of passing technical skills, it is necessary to add other variables, so that the results of passing technical skills increase even more.